Mitigating human-human collaboration problems using software agents - Ahmed M.; Ahmad M.S.; Yusoff M.Z.M. (2023)
In this paper, we demonstrate the use of autonomous agents to assist humans in complying with the schedule of a collaborative work process. Software agents take over the tasks of communicating between agents and reminding and alerting humans in complying with scheduled tasks. While the FIPA agent communication language implements communication exchanges between agents, an interface for each agent implements the communication between humans and agents. Such interface provides a convenient means for humans to delegate mundane tasks to software agents. 2010 Springer-Verlag.